Water Quality of Situ Rampones, Serang Regency - Forcep Rio Indaryanto; Melisah Melisah; Dedi Trimulya (JURNAL PERIKANAN DAN KELAUTAN, 2017)
Situ Rampones is upstream waters located in Sindang Mandi Village, Baros District, Serang Regency, Banten Province. This situation is used for public baths and household needs, such as drinking, cooking, washing up to irrigation of paddy fields in the surrounding sub-districts. The purpose of this research is to know Situ Rampones water quality. The study was conducted in March-May 2016 at six stationsi i.e inlet, bath room, bathhouse, outlet, 5 meter after outlet and 10 meter after outlet. Situ Rampones waters temperatures range from 25.6 to 28.23ºC, pH ranges from 7.75 to 8.28, DO ranges from 4.2 to 4.47 mg / L, NO2 ranges from 0 to 0.17, NO3 is 0, COD ranged from 4.43 to 5.07 mg / L and BOD ranged from 3.63 to 4.8 mg / L. Situ Rampones into the category of light contaminated waters.